Development of the National Economies and the Foreign Trade Relations between Ukraine and Bulgaria (In the Period 2005-2014) - Iliev, Dragomir Angelov; Neykov, Yordan Iliev (Journal of Empirical Studies, 2016)
The paper presents an analysis of the trends in the national economies of Bulgaria and Ukraine based on general macroeconomic indicators. An emphasis is put on the foreign trade between the two countries in the context of the global economic crisis and the crisis related to Ukraine’s territorial integrity. The analysis of the foreign trade between Bulgaria and Ukraine covers the main commodity groups in terms of their importance for the two economies.